Amino functionalized zeolitic tetrazolate framework (ZTF) with high capacity for storage of carbon dioxide - Panda, Tamas; Pachfule, Pradip; Chen, Yifei; Jiang, Jianwen; Banerjee, Rahul (Chemical Communications, 2011)
A three dimensional -NH(2) functionalized Zeolitic Tetrazolate Framework (ZTF-1) has been reported. The framework adopts a dia topology (M-L-M angle is close to 156 degrees). ZTF-1 shows high CO(2) (273 K) and H(2) (77 K) uptake due to the presence of the free -NH(2) group and uncoordinated tetrazolate nitrogen.